A Growth and Yield Model for Eucalyptus benthamii in the Southeastern United States. Issue 1 (5th November 2019) - Hall, Kevin B; Stape, Jl; Bullock, Bronson P; Frederick, Doug; Wright, Jeff; Scolforo, Henrique F; Cook, Rachel
Abstract: In recent Eucalyptus cold-tolerance trials, E. benthamii has shown good growth rates as well as cold tolerance for USDA Plant Hardiness Zones 8 and 9. This study developed growth and yield models for E. benthamii in the southeastern United States. A network of 182 temporary sample plots of E. benthamii ranging in age from 1.5 to 13.3 years was established, and inventory data were collected. Site quality was determined by fitting a polymorphic site index curve, whereas a function for stand basal area based on age, dominant height, and site occupancy was fitted. Stand-level volume and dry-weight biomass prediction equations were fitted as a function of dominant height and basal area. Based on the growth and yield model results, mean annual increments ranged from 26.4 m 3 ha –1 year –1 at rotation age 6 years on the best sites to 13.7 m 3 ha –1 year –1 at rotation age 10 years on the poorest sites. This is the first published set of management-oriented models for land managers considering planting E. benthamii in the southeastern United States.